Bankers and Plato's Cave Shadow and Substance - Wriston, Walter B. (Tufts Archival Research Center, 2007)
The document was created from the speech, "Bankers and Plato's Cave Shadow and Substance," written by Walter B. Wriston for the American Bankers Association on 10 October 1983. The original speech is located in MS134.001.005.00016.